Chemokines SNPs in HIV-1+ Patients and Healthy Controls from Northeast Brazil: Association with Protection against HIV-1 Infection. - Celerino da Silva, Ronaldo; Victor Campos Coelho, Antonio; Cláudio Arraes, Luiz; André Cavalcanti Brandão, Lucas; Lima Guimarães, Rafael; Crovella, Sergio (Curr HIV Res, 2016)
BACKGROUND: HIV-1 virus is known to infect the host mainly through CD4+ T-lymphocyte cells, by interactions among the viral envelope proteins, CD4 receptor and HIV-1 coreceptors, such as chemokines receptors. Variations in the genes encoding HIV-1 coreceptors and their natural ligands have been shown to modify HIV-1 infection susceptibility and disease progression. METHODS AND RESULTS: We analysed the distribution of SNPs in chemokines (CCL3, CCL4, CCL5, CXCL12) and chemokine receptor (CXCR6) genes, in 268 HIV-1 infected patients (HIV-1+) and 221 healthy controls from Northeast Brazil, and their possible connection with susceptibility to HIV-1 infection. The genotyping were performed through allele specific fluorogenic probes using real time PCR. We observed that the T alleles and AT genotype of rs1719153 CCL4 SNP were more frequent in healthy controls (19.8% and 35.0%, respectively) than in HIV-1+ patients (T allele: 14.1%; OR=0.67; 95%CI=0.47-0.95; p-value=0.020; and AT genotype: 24.4%; OR=0.61; 95%CI=0.40- 0.93; p-value=0.021) after correcting for age and sex. The rs1719134 (CCL3) and rs1719153 (CCL4) SNPs presented linkage disequilibrium (D'=0.83). The AT haplotype frequency was increased in healthy controls (17.3%) in relation to HIV-1+ patients (11.0%; OR=0.62; 95%CI=0.42-0.93; p-value=0.020). CONCLUSION: Since our results revealed an increased frequency of alleles and genotypes of CCL3/CCL4 SNPs and haplotype (CCL3-CCL4) among healthy controls, we suggest that these variations might have a potential protective role against HIV-1 infection.